Photoinduced formal [4 + 2] cycloaddition of two electron-deficient olefins and its application to the synthesis of lucidumone - Zhezhe Xu; Weibo Peng; Jiarui Huang; Jinhui Shen; Jing-Jing Guo; Anhua Hu (Nature Communications)
Abstract Electronically mismatched Diels−Alder reaction between two electron-deficient components is synthetically useful and yet underdeveloped under thermal conditions. Herein, a photoinduced formal [4 + 2] cycloaddition of enone with a variety of electron-deficient dienes is described. Key to the success of this stepwise methodology relies on a C − C bond cleavage/rearrangement of the cyclobutane based overbred intermediate via diversified mechanistic pathways. Based on this annulation method, total synthesis of lucidumone is achieved in nine steps.